Portion size normality and additional within-meal food intake: two crossover laboratory experiments. Issue 4 (6th September 2019) - Haynes, Ashleigh; Hardman, Charlotte A.; Halford, Jason C. G.; Jebb, Susan A.; Robinson, Eric
Abstract: Reducing food portion size could reduce energy intake. However, it is unclear at what point consumers respond to reductions by increasing intake of other foods. We predicted that a change in served portion size would only result in significant additional eating within the same meal if the resulting portion size was no longer visually perceived as 'normal'. Participants in two crossover experiments (Study 1: n 45; Study 2: n 37; adults, 51 % female) were served different-sized lunchtime portions on three occasions that were perceived by a previous sample of participants as 'large-normal', 'small-normal' and 'smaller than normal', respectively. Participants were able to serve themselves additional helpings of the same food (Study 1) or dessert items (Study 2). In Study 1 there was a small but significant increase in additional intake when participants were served the 'smaller than normal' compared with the 'small-normal' portion ( m difference = 161 kJ, P = 0·002, d = 0·35), but there was no significant difference between the 'small-normal' and 'large-normal' conditions ( m difference = 88 kJ, P = 0·08, d = 0·24). A similar pattern was observed in Study 2 ( m difference = 149 kJ, P = 0·06, d = 0·18; m difference = 83 kJ, P = 0·26, d = 0·10). However, smaller portion sizes were each associated with a significant reduction in total meal intake. The findings provide preliminary evidence that reductions that result in portions appearing 'normal' in size may limit additional eating, but confirmatory research is needed.